Association of SORD mutation with autosomal recessive asymmetric distal hereditary motor neuropathy - Majed Alluqmani; Sulman Basit (BMC, 2022)
Abstract Background The aim of this study was to identify the underlying genetic defect in a family segregating autosomal recessive asymmetric hereditary motor neuropathy (HMN). Asymmetric HMN has not been associated earlier with SORD mutations. Methods For this study, we have recruited a family and collected blood samples from affected and normal individuals of a family. Detailed clinical examination and electrophysiological studies were carried out. Whole exome sequencing was performed to detect the underlying genetic defect in this family. The potential variant was validated using the Sanger sequencing approach. Results Clinical and electrophysiological examination revealed asymmetric motor neuropathy with normal nerve conduction velocities and action potentials. Genetic analysis identified a homozygous mononucleotide deletion mutation (c.757delG) in a SORD gene in a patient. This mutation is predicted to cause premature truncation of a protein (p.A253Qfs*27). Conclusions Interestingly, the patient with homozygous SORD mutation demonstrates normal motor and nerve conduction velocities and action potentials. The affected individual describes in this study has a unique presentation of asymmetric motor neuropathy predominantly affecting the right side more than the left as supported by the clinical examination. This is the first report of SORD mutation from Saudi Arabia and this study further expands the phenotypic spectrum of SORD mutation.